The end of poverty: economic possibilities for our time - Sachs, Jeffrey (Penguin Books, 2006)
A respected international economic advisor and the director of The Earth Institute shares a wide-spectrum theory about how to enable economic success throughout the world, identifying the different categories into which various nations fall in today's economy while posing solutions to top political, environmental, and social problems that contribute to poverty. [The author] sets the stage by drawing a ... conceptual map of the world economy and the different categories into which countries fall. Then ... he explains why, over the past two hundred years, wealth has diverged across the planet in the manner that it has and why the poorest nations have been so markedly unable to escape the cruel vortex of poverty. The groundwork laid, he explains his methods for arriving ... at a holistic diagnosis of a country's situation and the options it faces. Rather than deliver a worldview to readers from on high, [the author] leads them along the learning path he himself followed, telling the ... stories of his own work in Bolivia, Poland, Russia, India, China, and Africa as a way to bring readers to a broad-based understanding of the array of issues countries can face and the way the issues interrelate. He concludes by drawing on everything he has learned to offer an integrated set of solutions to the interwoven economic, political, environmental, and social problems that most frequently hold societies back. In the end, he leaves readers with an understanding, not of how daunting the world's problems are, but how solvable they are - and why making the effort is a matter both of moral obligation and strategic self-interest